2018
DOI: 10.1128/aem.01300-18
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dechlorination of Polychlorinated Biphenyls in Dehalococcoides mccartyi CG1

Abstract: Reductive dehalogenation mediated by organohalide-respiring bacteria plays a critical role in the global cycling of organohalides. Nonetheless, information on the dehalogenation enantioselectivity of organohalide-respiring bacteria remains limited. In this study, we report the enantioselective dechlorination of chiral polychlorinated biphenyls (PCBs) by CG1. CG1 preferentially removed halogens from the (-)-enantiomers of the three major environmentally relevant chiral PCBs (PCB174, PCB149, and PCB132), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 54 publications
2
28
1
1
Order By: Relevance
“…A recent study has suggested that Synechocystis sp. strain PCC 6803 does not produce siderophores, and its TBDRs mediate the uptake of free iron and ferric-siderophores produced by other bacteria (xenosiderophore) 48 . In addition to all of the above, considering there are 74 TBDR-like genes in the SYK-6 genome, TBDRs of SYK-6 may mediate the uptake of free iron and xenosiderophore.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested that Synechocystis sp. strain PCC 6803 does not produce siderophores, and its TBDRs mediate the uptake of free iron and ferric-siderophores produced by other bacteria (xenosiderophore) 48 . In addition to all of the above, considering there are 74 TBDR-like genes in the SYK-6 genome, TBDRs of SYK-6 may mediate the uptake of free iron and xenosiderophore.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Zhao et al reported a high abundance of organohalide-respiring bacteria, including Dehalococcoides , Dehalobium , Dehalobacter , Desulfitobacterium , and Sulfurospirillum , in a conventional WWTP. Debromination of PBDEs has been previously reported by at least one member of each of these genera. , These findings indicate that wastewater sludge likely contains diverse anaerobic PBDEs-debrominating microorganisms; additional work is needed to identify and characterize these microorganism as well as the biological processes responsible for anaerobic biotransformation of PBDEs in wastewater sludge.…”
Section: Fate Of Hfrs In Biological Treatment Systemsmentioning
confidence: 76%
“…Debromination of PBDEs has been previously reported by at least one member of each of these genera. 170,171 These findings indicate that wastewater sludge likely contains diverse anaerobic PBDEs-debrominating microorganisms; additional work is needed to identify and characterize these microorganism as well as the biological processes responsible for anaerobic biotransformation of PBDEs in wastewater sludge.…”
Section: Fate Of Hfrs In Biological Treatment Systemsmentioning
confidence: 99%
“…For the enantioselective analyses of chiral PCBs, two different enantioselective columns were utilized to separate PCB enantiomers as previously described. , A CP-Chirasil-Dex CB column (25 m × 0.25 mm × 0.25 μm film thickness; Agilent J&W Scientific) was used for the separation of PCB-84, PCB-91, PCB-95, PCB-132, PCB-135, PCB-136, PCB-149, PCB-174, and a BGB-172 column (30 m × 0.25 mm × 0.18 μm film thickness; Boecten, Switzerland) was used for the separation of PCB-183. The composition of chiral PCB enantiomers was quantified by using the enantiomeric fraction (EF) according to the following equation: EF = E1/(E1+E2), where E1 and E2 represented the peak areas of (+)-enantiomers and (−)-enantiomers, respectively.…”
Section: Materials and Methodsmentioning
confidence: 99%